2021
DOI: 10.4236/ojmp.2021.102003
|View full text |Cite
|
Sign up to set email alerts
|

Stalking of Healthcare Professionals by Their Clients: The Prevalence, Motivation, and Effect

Abstract: It is proposed that healthcare professionals are prone to be stalked by their patients, but many feel ashamed to talk about it, believing that they might have done something to warrant the stalking. We undertook a rigorous review of the literature with the primitive goal of highlighting noteworthy issues on the stalking of healthcare professionals and psychologists by their patients. Databases such as PubMed and Google Scholar were searched to collate articles and studies on the topic with the keywords "stalke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Healthcare workers are frequently the targets of harassment, which can last for a few weeks to several years and take the form of unwanted phone calls, letters, direct contact, threats, secret or open monitoring/ surveillance, etc. (Manunza et al, 2018;Bulut et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare workers are frequently the targets of harassment, which can last for a few weeks to several years and take the form of unwanted phone calls, letters, direct contact, threats, secret or open monitoring/ surveillance, etc. (Manunza et al, 2018;Bulut et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Mental health has been the primary focus of studies on the (cyber) obsessive monitoring of healthcare workers (Manunza et al, 2018;Bulut et al, 2021). According to a study by McKenna et al (2003), patients threatened nurses verbally 35% of the time, sexually harassed them verbally 30% of the time, physically threatened them 29% of the time, and stalked them 3.8% of the time in their first years of employment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unclear whether there are occupational roles within the same organizational context that are more at risk of victimization. Indeed, there are professions that are more concerned with health care, that are more in touch with the patient's body, and that need to intervene in the containment of Petch (2006) and Bulut, Usman, and Nazir (2021) attempt to describe the main reasons that may underlie the fact that HCPs can be victims of stalking and summarizes them in two main explanations: (i) These professionals come into contact with people in need and can easily fall prey to projections of affection and internalized relationships; (ii) The unrealistic expectations of certain patients can be undermined by the demands of daily work, leading to stalking as a means of seeking attention or seeking retribution for the burden of responsibility for one's own health or the well-being of loved ones. These factors are never entirely under anyone's control.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in a large study across the 28 member states of the European Union (EU): the report on the findings from a survey of 42,000 women revealed that 18% of them have experienced some form of stalking since the age of 15 (European Union Agency for Fundamental Rights, 2014). Furthermore, due to the nature of work, stalking may occur more frequently among particular populations such as politicians (Every‐Palmer et al., 2015), healthcare professionals (Bulut et al., 2021), or celebrities (Willson et al., 2018). Previous studies also indicate that personal experience of stalking may be related to the perception of this phenomenon: as females are more likely to become the victims of stalking, they perceive certain stalking behaviors as unacceptable more often compared to males (Chan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%